2019
DOI: 10.1186/s12889-019-6756-7
|View full text |Cite
|
Sign up to set email alerts
|

Health issues in a Bangalore slum: findings from a household survey using a mobile screening toolkit in Devarajeevanahalli

Abstract: Background Slums are home to nearly one billion people in the world and are expanding at an exponential rate. Devarjeevanahalli is a large notified slum in Bangalore, South India which is characterised by poverty, overcrowding, hazardous living environment and social complexities. The poor living conditions not only affect the health of the people living there but also poses distinctive challenges to conducting health surveys. The purpose of this paper is to report the findings of a household surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…THULSI has already been used for screening purposes in a Bangalore slum. 8 THULSI consists of various screening tools and devices such as glucometers, weighing scales, tape measure, BP monitor, and a cuff. It also has an electronic component in the form of an android-based application that was used to collect the health survey on an electronic tablet.…”
Section: The Screening Toolkitmentioning
confidence: 99%
See 1 more Smart Citation
“…THULSI has already been used for screening purposes in a Bangalore slum. 8 THULSI consists of various screening tools and devices such as glucometers, weighing scales, tape measure, BP monitor, and a cuff. It also has an electronic component in the form of an android-based application that was used to collect the health survey on an electronic tablet.…”
Section: The Screening Toolkitmentioning
confidence: 99%
“…7 A study in a slum of Bangalore found that out of 3693 people that were screened, 35.5% had hypertension, 16.6% had diabetes, and 20.1% and 5.7% of these people were screened for the rst time in their lives for hypertension and diabetes, respectively. 8 Nationally, roughly 19.7% are overweight or obese, 25.8% have raised blood pressure, and 8.7% have raised blood glucose in India. 9,10,11 Therefore, previous research has highlighted two important NCD characteristics for the Indian slum population: higher than national rates of NCDS are found in slums and residents are often unaware of their condition.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,13 Several studies have been conducted to understand the spectrum, burden, treatment-seeking behavior and determinants of illnesses in urban slums. 14,15 Most of these researches studies focus on self-reported morbidity, have a small sample size and are limited to, acute illnesses, illnesses of maternal and child health. The few studies that have been conducted on non-communicable diseases (NCD) have a small sample size and are limited to the elderly population in a specific geographic location.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have been conducted on non-communicable diseases (NCD) have a small sample size and are limited to the elderly population in a specific geographic location. [14][15][16] Piramal Swasthya through its Ujjivan program runs fleet of a doctor-led mobile medical units (MMU) in 4 major cities of India. The program is aimed at catering to the health needs of urban slum dwellers, with a special focus on NCDs.…”
Section: Introductionmentioning
confidence: 99%
“…Urban poor people like living in a vicious circle. Between poor, uneducated, and sick, like a chain that is difficult to break 3,4 . Urban poor people tend to form their own colonies in urban slums.…”
Section: Introductionmentioning
confidence: 99%